Trois places pour le 26 - Legrand, Michel 1932-2019 (Intégrale Jacques Demy, 2008)
Yves Montand plays himself in this musical. He arrives in Marseilles by train to film his autobiography but in his spare time searches for his first love Mylène who is already married and has a daughter who dreams of starring in a musical. The film is seen as a retrospective on Demy's life and also Montand's